Interviews of Human Intelligence (HUMINT) Officers - Nunan, Jordan; Milne, Rebecca; Shawyer, Andrea; Walsh, Dave; Stanier, Ian (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.Intelligence led policing is deemed a proactive measure to counter criminal activity. The use of both overt and covert practices are used to support this proactive approach to policing England and Wales. There are a variety of methods that agencies can use to collect intelligence. First amongst collection capabilities is the discipline of HUMINT, the branch charged with eliciting intelligence through interaction with human sources, such as Covert Human Intelligence Sources (CHIS). The use of covert means can potentially disrupt, dismantle or prevent serious crime and its related organised crime networks. Therefore, it is a particularly important element of security. However, research is yet to explore the perceptions and experiences of gathering HUMINT within England and Wales. Hence, this research comprises of semi-structured interviews with practitioners who have worked within HUMINT. This provides an empirical exploration of the current successes and challenges in gathering intelligence, covering key topics such as training, rapport, intelligence gathering approaches, memory, and communication. The ethical challenges and preliminary findings will be discussed.
Keywords: 'HUMINT'; 'Intelligence'; 'Interviewing'; 'DSDS17 poster'; 'DSDS17'; 'Police Administration; Procedures and Practice'